FOAM CONCRETE ON THE BASIS FILLERS FROM RECYCLED MATERIALS - S-A. Y. Murtazaev; M. S. Saydumov; M. R. Hadgiev; V. H. Hadisov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The paper is devoted to the actual problem recycling crushing screenings brick battle and workmanship bricks using it as a fine aggregate in cellular foam concrete products.The paper presents the analysis of the environmental situation of the region and the results of a study of waste crushing brick fight to improve the utilization of the product technology in cellular-concrete products. A comparative study of traditional cellular gas concretes and foam concretes and concretes based on recycled sand.